A transparência pública nos Conselhos Regionais de Desenvolvimento (Coredes) do Rio Grande do Sul - Santos, Suélen Xavier dos (2022)
In the scope of public administration, transparency is a fundamental precept, through the information that is disclosed, society has the opportunity to exercise control over the State, participating and monitoring the actions undertaken by elected or not elected officials. In this sense, governance acts as a primary ally to transparency, guiding how to act correctly and serving as a means of preventing corruption. In search of guarantees of the smooth running of transparency with the help of governance, some mechanisms were created, such as the Fiscal Responsibility Law and the Access to Information Law, the latter acting as a way of putting into operation the principle of publicity so linked to public transparency, in order to make secrecy an exception. The State of Rio Grande do Sul, composed of 497 municipalities, seeking regional development, uses development councils as a way of giving voice to each region according to its needs, dividing the territory into 28 Regional Development Councils (Coredes) and these into 9 Functional Planning Regions. With a view to the importance of public transparency for social control and councils for municipalities, this study aimed to understand the main practices, developed by Coredes, that enable public transparency. In order to achieve this objective, a documental analysis of the Coredes sites was carried out, determining the level of transparency of each unit, followed by interviews with representatives of the councils. A correlation study was also carried out with the Socioeconomic Development Index - Idese of each region, for which tools such as content analysis and Microsoft Excel and SPSS software were used. With the results obtained, it was possible to perceive that although there is no legal obligation, Coredes show a certain willingness to disclose their actions because they perceive the growing interest of the population, so the councils also seek to apply some principles of public governance in their daily lives. In the Coredes Management Transparency Index - ITGC, the council that stood out was the Médio Alto Uruguai followed by Vale do Rio Pardo and Vale do Taquari tied for 2nd place and Vale do Rio dos Sinos in 3rd. When it came to the averages by Functional Development Region - RF, the best placed was RF2, which in comparison with its respective Idese obtained only the 4th best index, thus being able to infer that although the correlation has been shown to be direct, the ITGC is different from the Idese index, which may be affected by other local agents. In the semi-structured interviews, the respondents recognized the lack of transparency on their websites and/or pages and that the most expressive participation of the population takes place in the Popular Consultation, they still attributed a greater drop in participation to the Covid-19 pandemic. Regarding difficulties in managing the Coredes, the interviewees reported delays in the transfer of maintenance funds, difficulty in succession and use of Coredes as “political platforms”, in addition to a lack of interest from the young public.